HUBUNGAN DERAJAT SESAK DAN OBSTRUKSI SALURAN NAPAS DENGAN KUALITAS HIDUP PASIEN PPOK - Nadiya Aliyah Roselyn; Adhiputri, Artrien; Munawaroh, Siti; Aphridasari, Jatu (Fakultas Kedokteran, Universitas Palangka Raya, 2023)
Chronic Obstructive Pulmonary Disease (COPD) is still a national and global health problem. In 2018, COPD cases in Central Java ranked seventh. COPD is characterized by airway obstruction that leads to shortness of breath. This disease causes worsening of health conditions and affects quality of life. The purpose of this study was to determine the correlation between the dyspnea scale and the airflow limitation severity with the quality of life of COPD patients at UNS Hospital. The method used in this research was analytic observational study with cross sectional design. The subjects in this study were COPD patients at the Pulmonary Polyclinic of UNS Hospital in February-March who had fulfil the criterias. The sampling technique of this research was purposive sampling. Data were collected using the mMRC questionnaire, SGRQ-C questionnaire, and spirometry data from medical records. The obtained data were analyzed with the Spearman correlation test. Spearman correlation test for 37 respondents obtained a p-value of 0,001 and a correlation coefficient (r) of 0,527 for the dyspnea scale and quality of life variable, which means that both variables are significant and moderately correlated. As for the airflow limitation severity and quality of life variable, the p-value is 0,000 and the correlation coefficient (r) is 0,808, which means that the two variables are significant and very strongly correlated. There is a significant correlation between dyspnea scale with the quality of life and airflow limitation severity with the quality of life of COPD patients at UNS Hospital.